Optimizing Karawo Art-Based Digital Learning Media to Strengthen Local Cultural Identity - Mursidah Waty; Soesanto, Soesanto; Haryanto, Eko; Sugiarto, Eko (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
This study examines the optimization of digital learning media based on karawo art to strengthen local cultural identity. Karawo art, as an intangible cultural heritage rich in philosophical and aesthetic values, faces preservation challenges amidst the development of digitalization. The research uses a qualitative approach with a case study through in-depth interviews with 5 karawo artisans, 2 school principals, 5 arts and culture teachers, and 10 students in Gorontalo, as well as document analysis and field observations. The findings indicate that the use of digital technologies, such as online learning platforms, interactive media, and social media can motivate student learning compared to conventional methods. Thus, accelerating the process of knowledge transfer across generations and able to expand the reach of learning beyond the Gorontalo region. Digital integration also strengthens students' sense of cultural identity and enhances practical skills, despite challenges related to infrastructure readiness and limited digital competency among some teachers. The practical implications of this research emphasize the need for the development of a technology-based adaptive curriculum, ongoing teacher training, and the development of authentic digital content to ensure the survival and relevance of karawo art in the modern era. With these strategies, digitalization has the potential to become a humanistic instrument for preserving and actualizing karawo art for future generations.